Pengembangan Konseling Karir John Holland dengan Teknik Modeling untuk Meningkatkan Perencanaan Karir Peserta Didik - Nissa Aulia; Ni Ketut Suarni; I Ketut Dharsana (Jurnal Bimbingan dan Konseling Indonesia, 2022)
The examination of this research and development study aimed at This research is a research and development research and development. This manual was created to facilitate the counseling teacher in the hold of counseling services. The process of production based on the development model of 4D; those are define, design, development, and dissemination. BK teachers in implementing counseling services in schools. To validate the product, 3 lectures experts from FIP Undiksha and 2 counseling teachers participated as expert judges. The effectiveness of John Holland theory was tested in order to acknowledge its effectiveness by involving 10 students as the research subject. The total items of instruments was 22 items and it was used to test the content validity. The result revealed a good quality owned by John Holland theory guide book on each item. Thus, to answer the hypothesis proposed by this research, t-test was employed. The result of hypothesis test reveals the effectiveness from the use of the guidebook to improve the students’ carrier planning. The value of ES was 1.464, which is high ES category. Abstrak: Penyajian penelitian pengembangan ini bertujuan untuk menciptakan sebuah produk buu oanduan yang dapat berperan penting dalam memfasilitasi pelayanan BK di setiap sekolah. dalam proses pengembangan, model yang digunakan adalah model 4D yang terdiri dari : define, design, development, dan dissemination. Dalam proses penilaian instrument, 3 orang judges yang berasal dari dosen FIP UNdisha dan 2 orang guru konseling dipilih. Setelah kevalidan instrument diperoleh, 10 orang siswa yang berperan sebagai subjek penelitian dilibatkan untuk menguji efektifitas produk pengembangan teori John Holland. Hasil uji instrument menunujkkan validitas yang baik yang ditunjukkan oleh 22 butir item instrument yang digunakan untuk menilai validitas isi. , dinyatakan buku panduan teori John Holland memiliki validitas yang baik untuk setiap butirnya. Hasil dari data analisa menunjukkan bahwa hipotesis yang diajukan diterima dan buku panduan dinyatakan efektif untuk diterapkan. Untuk nilai ES= 1,464 yang termasuk kategori ES tinggi.